FORECASTING BUDGET REQUIREMENT FOR INDONESIAN ARMS MODERNISATION WITH INTERNATIONAL COST ESCALATION (ICE) - Maharani, Curie; Noor, Reyhan; Pratama, Sandy J; Wicaksono, Ganesh A. (UI Scholars Hub, 2026)
In 2021, the question